Pengaruh Kepuasan Konsumen Terhadap Keputusan Pembelian Berulang Air Minum di Depot 3 Putri Kelurahan Waihoka - Zakarias Talpatty; William George Louhenapessy; Geradin Rehatta (Jurnal Pendidikan Geografi Unpatti, 2025)
Customer satisfaction is a key factor influencing repeat purchase decisions, particularly in the refill drinking water industry. This study aims to analyze the influence of customer satisfaction on repeat purchase decisions at Depot 3 Putri, Waihoka Subdistrict. The study employed a quantitative approach using a survey method, with data collected through questionnaires distributed to 100 respondents. Data analysis was conducted using simple linear regression with the assistance of SPSS 22. The results showed that customer satisfaction had a significant effect on repeat purchase decisions, as indicated by a t-value of 11.623, which is greater than the t-table value of 1.66055, and a significance level of 0.000 < 0.05. The regression model obtained was Y = 9.302 + 0.678X, indicating that each one-unit increase in customer satisfaction leads to a 0.678 increase in repeat purchase decisions. The R Square value of 0.580 suggests that 58% of the variation in repeat purchase decisions is explained by customer satisfaction, while the remaining 42% is influenced by other factors not examined in this study. In conclusion, the higher the level of customer satisfaction with service and water quality, the greater the likelihood of repeat purchases.